2016
DOI: 10.1186/s12889-016-3484-0
|View full text |Cite
|
Sign up to set email alerts
|

The early life nutritional environment and early life stress as potential pathways towards the metabolic syndrome in mid-life? A lifecourse analysis using the 1958 British Birth cohort

Abstract: BackgroundLifecourse studies suggest that the metabolic syndrome (MetS) may be rooted in the early life environment. This study aims to examine the pathways linking early nutritional and psychosocial exposures and the presence of MetS in midlife.MethodsData are from the National Child Development Study including individuals born during 1 week in 1958 in Great Britain and followed-up until now. MetS was defined based on the National Cholesterol Education Program Adult Treatment Panel III classification. Mother’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 61 publications
3
39
0
Order By: Relevance
“…Better educated women from the middle-income sites likely had/have more money to afford obesogenic, westernised foods and over their lifetimes, may have engaged in less exercise, as educational attainment may have allowed them to ‘escape’ physically strenuous jobs. Consistent with other research, 32 early life adversity was associated to higher prevalence estimates of MetS; however, this association was only observed in men, whereas it has been observed in both men and women elsewhere. 32 The strong context specificity of our findings highlights the utility of using MOB to identify unique admixtures that might have been overlooked with traditional statistical techniques and/or would have been impossible to identify without a very large sample size.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Better educated women from the middle-income sites likely had/have more money to afford obesogenic, westernised foods and over their lifetimes, may have engaged in less exercise, as educational attainment may have allowed them to ‘escape’ physically strenuous jobs. Consistent with other research, 32 early life adversity was associated to higher prevalence estimates of MetS; however, this association was only observed in men, whereas it has been observed in both men and women elsewhere. 32 The strong context specificity of our findings highlights the utility of using MOB to identify unique admixtures that might have been overlooked with traditional statistical techniques and/or would have been impossible to identify without a very large sample size.…”
Section: Discussionsupporting
confidence: 91%
“… 40 Finally, we did not collect individual dietary data or data on the early nutritional environment. 32 …”
Section: Discussionmentioning
confidence: 99%
“…Although the available evidence did not support a direct link between MPBW and offspring's BP, this review identified indications for an indirect or mediated association: As shown by our adjustment handling, offspring's anthropometry may almost entirely explain the relation between MPBW and offspring's BP. Similarly, other thematically close, recently published studies point to such an indirect relation of MPBW with cardiometabolic risk factors such as metabolic syndrome (including BP, high‐density lipoprotein, triglycerides, waist circumference, and HbA1c; Delpierre et al, ) and cardiac structure (including left ventricular mass, left ventricular mass index, relative wall thickness, fractional shorting, and eccentric left ventricular hypertrophy; Toemen et al, ); the association attenuated into nonsignificance after adding participants' BMI to the multivariate model. Previous studies already described a strong relation of MPBW with higher rates of offspring's overweight or obesity (Pacce et al, ; Yu et al, ), whereas childhood BMI is in turn related to cardiometabolic outcomes (Black et al, ; Di Bonito et al, ), including BP (Friedemann et al, ; Onis et al, ).…”
Section: Discussionmentioning
confidence: 85%
“…Such early life parental and physical experiences can influence individual sociality in a number of ways, including future parental behaviour (Margulis et al, 2005;Champagne et al, 2006;Maestripieri et al, 2006;Champagne, 2008;Kappeler & Meaney, 2010), affiliative tendencies and partner preferences (Uchino, 2009;Hawkley et al, 2012;Branchi et al, 2013;Feldman et al, 2013;Ilany & Akçay, 2016;Tung et al, 2016;Jarrett et al, 2018), aggressive tendencies and dominance behaviour (Bastian et al, 2002;Sachser et al, 2011) and emotional regulation (Weaver & de Waal, 2003;Weaver et al, 2004;Allen et al, 2007;Branchi et al, 2009;Clay & de Waal, 2013). Early life experience can also influence survival (Tung et al, 2016;Alberts, 2018), reproductive success (Altmann, 1991;Margulis et al, 2005;Douhard et al, 2014), and risk of particular disease (Delpierre et al, 2016). This leads to the clear possibility that early life conditions influence both sociality and fitness simultaneously, and potentially drive a spurious correlation between them in adults.…”
Section: Impact Of Early Life Experience On Social Ties and Fitnessmentioning
confidence: 99%